Broad ligament fibroid-clinical presentation and surgical challenges: a case series - Tauro, Sheral Raina; Devi, Ningthoujam Priyalaxmi; Meetei, Laishram Trinity; Sen, Sayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine leiomyomas are benign monoclonal tumors originating from smooth muscle tissue. Their classification is based on anatomical location, with each type presenting unique surgical challenges, particularly in cases involving large, long-standing fibroids in atypical positions. These challenges often stem from limited access to the operative field, distorted pelvic anatomy, difficulty in performing surgical repairs, and increased risk of blood loss. Managing such complex fibroids requires both surgical expertise and refined technique, especially when performing intricate hysterectomies. In this case series of five patients, we examine the varied presentations of broad ligament fibroids, associated clinical findings, and the operative difficulties encountered. Tailored approaches are essential, as each fibroid type demands a specific surgical strategy. Preoperative imaging for fibroid mapping, along with ureteric stenting when indicated, plays a crucial role in minimizing intraoperative complications. Adherence to established surgical principles ensures optimal outcomes, reduces the risk of urinary tract injury, and helps control blood loss during surgery.